Chronic Recurrent Multifocal Osteomyelitis (CRMO): A Study of 12 Cases from One Institution and Literature Review. (3rd September 2022) - Chang, Eric; Vickery, Jasmine; Zaiat, Nadeen; Sallam, Eman; Hanan, Abdul; Baker, Scott; Alhamar, Mohamed; Poulik, Janet; Demian, Ereny; Shehata, Bahig M
Abstract: Background: CRMO is a sterile auto inflammatory bone disease that affects the pediatric population. Recently, single gene mutations in LPIN2, DIRA, and IL1RN have been reported in murine models of CRMO. Materials and methods: The medical records and histopathological slides of twelve patients were reviewed. Results: The diagnosis was determined by multiple lesions, imaging, negative cultures, bone biopsy, and lack of antibiotic response. Biopsy showed early neutrophilic infiltrates, and older lesions showed lymphoplasmacytic infiltrates and fibrosis. Patients were treated with anti-inflammatory medication with some lesions completely resolving. Conclusion: Bone biopsy aids the diagnosis of CRMO in correlation with clinical presentation, imaging, and culture findings. Our findings indicate the kinetics of CRMO is not well defined and the fibrosis may be reached after months, in contrast to the previously reported several years. We hope that these genetic mutations can be further studied in human models to describe the genetics behind CRMO.